ANALISIS PENGARUH ADSORBENT PADAT TERHADAP KUALITAS KANDUNGAN BIOGAS - Harmiansyah; Lathifa Putri Afisna; Sugatra Dwi Atmaja; Fitrah Qalbina; Rustam Efendi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2022)
The population is getting bigger every year as population growth increases, with population growth the use of fossil energy becomes high so that energy availability is increasingly limited. Renewable energy is one way to overcome the diminishing availability of energy, one of which is biogas. Biogas is a renewable gas fuel produced from the fermentation process of organic matter by anaerobic bacteria in a vacuum, biogas is also included in the energy category which is environmentally friendly and easy to use. Optimization of biogas performance can be carried out by purifying the biogas content using the adsorption method. In this study using natural zeolite adsorbentts and activated carbon with 3 mass variations, namely 250, 500 and 750 grams. Based on the results of the tests that have been carried out, the adsorbentt has an effect on the biogas content, the more adsorbentt used, the greater the CH4 gas (at 250 grams it is 46.29%, 500 grams is 48.33%, and 750 grams is 51.84%) followed by a decrease in CO2 (at 250 grams of 47.38%, 500 grams of 47.47%, and 750 grams of 43.02%) and the better the quality of biogas. The minimum pressure required to pass through the 750 gram adsorbentt is 7 mbar (700 Pa) or the minimum pressure provided by the floating drum.